Hidden beneath the arid Patagonian lowlands: ecological and conservation considerations to protect a hotspot of subterranean biodiversity - Marconi Souza-Silva; Hernán Augusto Iuri; Marcela Alejandra Mattioni; Robson de Almeida Zampaulo; Willians Porto; Gabriel Redonte; Mariana Paparas; Silvia Sicilia; Rodrigo Lopes Ferreira (Community Ecology, 2026)
To highlight the significance of unique subterranean ecosystems, the concept of Hotspots of Subterranean Biodiversity (HSB) was introduced to designate caves or cave systems with exceptionally high richness of cave-restricted species, which often require urgent conservation measures. The Cuchillo Curá cave system, the largest in Patagonia (Argentina) and the richest in cave-restricted fauna, exemplifies such a hotspot, although it remains poorly studied. In this review, we assess the richness of troglobitic species, identify environmental variables that shape their distribution, and highlight the conservation importance of the system. We documented 26 troglobitic and stygobitic species, combining direct sampling with published records. This fauna encompasses a broad taxonomic range, including Arachnida (8 species), Crustacea (6 species), Collembola (4 species), Diplura (3 species), and single representatives of Diplopoda, Symphyla, Coleoptera, Auchenorrhyncha, and Zygentoma. Most taxa are terrestrial (22), with only four aquatic representatives. Species distribution patterns were associated with microhabitat heterogeneity, distance from cave entrances, temperature, and relative humidity. Shelter diversity and thermal variation emerged as key predictors of species richness. The Cuchillo Curá system hosts a highly specialized subterranean fauna, marked by remarkable morphological and ecological adaptations to cave life. However, this fragile ecosystem is increasingly threatened by mining, tourism, groundwater depletion, and the advancing effects of climate change. Protecting the system is therefore essential not only for safeguarding Patagonia’s subterranean biodiversity but also for preserving a unique component of the region’s natural heritage.